The Role of Digitalization and Sustainable Agriculture in Building Resilient Food Systems Post-COVID-19 - Karna, Poonam Kumari Labh (Lembaga Yasin AlSys, 2025)
The COVID-19 pandemic has exposed flaws in the world's food systems, highlighting how urgent sustainability and resilience are. In the post-pandemic period, this study looks at how digitalisation and sustainable farming methods might improve food systems. It examines data and case studies with a focus on Nepal to evaluate how eco-friendly farming practices and digital tools affect food security, supply chain effectiveness, and agricultural output. Incorporating digital technologies like smart supply chain management, mobile-based market access, and precision farming can improve agricultural results, according to the study. These developments optimise resource utilisation, lower post-harvest losses, and assist farmers in making well-informed decisions. Sustainable agricultural methods, such as climate-smart approaches and organic farming, also help to preserve the environment while guaranteeing the stability of food production over the long run. Results show that digitalisation greatly improves the resilience of food systems, especially in developing countries like Nepal, when paired with sustainable practices. However, for widespread use, issues like inadequate internet infrastructure, gaps in regulation, and farmer education must be resolved. The study ends with legislative recommendations to speed up the digital transformation of agriculture, such as funding for digital infrastructure, training initiatives for farmers, and laws that encourage sustainable practices. In the post-COVID-19 era, governments and stakeholders can create resilient food systems that can resist future upheavals, guarantee food security, and stimulate agricultural growth by boosting digital innovation and sustainability.